Integration Of Traditional Islamic Boarding School Values and Modern Philanthropic Practices At The Darunnajah Amil Zakat Institution (LAZ) - Rinaldi Permana Putra; Wildan Syifauddin; Muhammad Iman Kurniawan (Jurnal Ilmu Sosial dan Humaniora, 2026)
The relationship between tradition and modernity in Islamic studies is often framed as a dichotomy, as if the two cancel each other out. This study offers a different reading by positioning them as an integrable relationship. The objective is to describe how the traditional values of the pesantren are negotiated with modern philanthropic practices at the Darunnajah Zakat Institution (LAZ), and to formulate the resulting pattern of integration. The study uses a qualitative descriptive approach. Data were gathered from four purposively selected informants, comprising two institutional managers and two program beneficiaries, through in-depth interviews, observation, and analysis of institutional documents, then examined thematically. The findings show that pesantren values such as sincerity, blessing, the authority of the kiai, and the ethic of self-reliance do not disappear when the institution adopts modern instruments such as corporate governance, digital fundraising, and productive zakat. The Kampung Sukses, MSMEs Productive Zakat program, which channels business capital to eight micro-enterprises, serves as a concrete example of this integration. Tradition functions as the spirit that grants legitimacy and direction, while modernity serves as the instrument that widens reach and accountability. The pattern is not a dichotomy but a functional coexistence. These findings lend support to the thesis of multiple modernities in the context of pesantren-based Islamic philanthropic institutions and propose a governance model that unites the value of worship with modern professionalism.